Upaya Meningkatkan Kedisiplinan Mengajar Guru Melalui Konseling Kelompok Dalam Supervisi Akademik Di SD Negeri 1 Ngadiharjo - Widati, Sri (Science and Education Journal (SICEDU), 2022)
The discipline attitude of a teacher affects professionalism in playing teaching tasks. Some of the problems that occur regarding the disciplinary behavior of teachers are still found including coming late to school, late for class and lack of discipline in class attendance. If this condition continues and does not get a good solution, it is possible that it can affect student learning activities. In response to this problem, school action research (PTS) was carried out through group counseling in academic supervision at schools. In this case, the focus of the research is how to improve teacher teaching discipline through group counseling in academic supervision at SD Negeri Ngadiharjo 1. The subject of the research is the competence of teachers at SD Negeri 1 Ngadiharjo, with qualitative and descriptive comparative data collection. The results showed that efforts to improve teacher teaching discipline increased with the implementation of actions in cycle I and cycle II through group counseling in academic supervision at SD Negeri Ngadiharjo 1.